Effects of preeclampsia and eclampsia on maternal metabolic and biochemical outcomes in later life: a systematic review and meta-analysis - Alonso-Ventura, Vanesa (2020)
Objective: To evaluate the association between preeclampsia (PE) and eclampsia (E) on subsequent metabolic and biochemical outcomes. Methods: Systematic review and meta-analysis of observational studies. We searched five engines until November 2018 for studies evaluating the effects of PE/E on metabolic and biochemical outcomes after delivery. PE was defined as presence of hypertension and proteinuria at >20 weeks of pregnancy; controls did not have PE/E. Primary outcomes were blood pressure (BP), body mass index (BMI), metabolic syndrome (MetS), blood lipids and glucose levels. Random effects models were used for meta-analyses, and effects reported as risk difference (RD) or mean difference (MD) and their 95% confidence interval (CI). Subgroup analyses by time of follow up, publication year, and confounder adjustment were performed. Results: We evaluated 41 cohorts including 3300 PE/E and 13,967 normotensive controls. Women were followed up from 3 months after delivery up to 32 years postpartum. In comparison to controls, PE/E significantly increased systolic BP (MD = 8.3 mmHg, 95%CI 6.8 to 9.7), diastolic BP (MD = 6.8 mmHg, 95%CI 5.6 to 8.0), BMI (MD = 2.0 kg/m2; 95%CI 1.6 to 2.4), waist (MD = 4.3 cm, 95%CI 3.1 to 5.5), waist-to-hip ratio (MD = 0.02, 95%CI 0.01 to 0.03), weight (MD = 5.1 kg, 95%CI 2.2 to 7.9), total cholesterol (MD = 4.6 mg/dL, CI 1.5 to 7.7), LDL (MD = 4.6 mg/dL; 95%CI 0.2 to 8.9), triglycerides (MD = 7.7 mg/dL, 95%CI 3.6 to 11.7), glucose (MD = 2.6 mg/dL, 95%CI 1.2 to 4.0), insulin (MD = 19.1 pmol/L, 95%CI 11.9 to 26.2), HOMA-IR index (MD = 0.7, 95%CI 0.2 to 1.2), C reactive protein (MD = 0.05 mg/dL, 95%CI 0.01 to 0.09), and the risks of hypertension (RD = 0.24, 95%CI 0.15 to 0.33) and MetS (RD = 0.11, 95%CI 0.08 to 0.15). Also, PE/E reduced HDL levels (MD = –2.15 mg/dL, 95%CI –3.46 to −0.85). Heterogeneity of effects was high for most outcomes. Risk of bias was moderate across studies. Subgroup analyses showed similar effects as main analyses. Conclusion: Women who had PE/E have worse metabolic and biochemical profile than those without PE/E in an intermediate to long term follow up period. ©